THE INFLUENCE OF MATHEMATICS ACHIEVEMENT ON FURTHER STUDY PLANS IS REVIEWED FROM LEARNING INTEREST AND LEARNING MOTIVATION - Lusi Luthfiati Ramdliyani; Surya Amami Pramuditya (Journal Of Education, 2026)
Mathematics achievement is one of the important indicators in assessing students' academic readiness to continue their education to a higher level. This study aims to analyze the influence of mathematics achievement on students' further study plans, both directly and indirectly through learning interests and learning motivation as mediating variables. This study uses a quantitative approach with the type of explanatory research. The subject of the study was 80 students of grade XII Science in one of the state aliyah madrasas. Mathematics achievement data was obtained from the report cards of Compulsory Mathematics and Advanced Mathematics, while data on learning interests, learning motivation, and further study plans were collected through a Likert scale questionnaire. Data analysis was carried out using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the study showed that mathematics achievement had a positive and significant effect on students' learning interests, learning motivation, and further study plans. Learning motivation has a significant effect on further study plans and acts as a partial mediating variable in the relationship between mathematics achievement and further study plans. On the other hand, interest in learning had no significant effect on the further study plan and did not function as a mediating variable. These findings confirm that learning motivation has a more dominant role than learning interest in determining students' further study planning.